Characterization of mating type genes in heterothallic Neonectria species, with emphasis on N. coccinea, N. ditissima, and N. faginata. (2nd September 2020) - Stauder, Cameron M.; Garnas, Jeff R.; Morrison, Eric W.; Salgado-Salazar, Catalina; Kasson, Matt T.
ABSTRACT: Neonectria ditissima and N. faginata are canker pathogens involved in an insect-fungus disease complex of American beech ( Fagus grandifolia ) in North America commonly known as beech bark disease (BBD). In Europe, both N. ditissima and N. coccinea are involved in BBD on European beech ( Fagus sylvatica ). Field observations across the range of BBD indicate ascospores to be the dominant spore type in the environment. Several studies report a heterothallic (self-sterile) mating strategy for Neonectria fungi, but one study reported homothallism (self-fertility) for N. ditissima . As such, investigations into mating strategy are important for understanding both the disease cycle and population genetics of Neonectria . This is particularly important in the United States given that over time N. faginata dominates the BBD pathosystem despite high densities of nonbeech hosts for N. ditissima . This study utilized whole-genome sequences of BBD-associated Neonectria spp. along with other publicly available Neonectria and Corinectria genomes and in vitro mating assays to characterize mating type (MAT) locus and confirm thallism for select members of Neonectria and Corinectria . MAT gene–specific primer pairs were developed to efficiently characterize the mating types of additional single-ascospore strains of N. ditissima, N. faginata, and N. coccinea and several other related species lacking genomic data. These assays also confirmed the sexual compatibility among N. ditissima strains from different plant hosts. Maximum likelihood phylogenetic analyses of both MAT1-1-1 and MAT1-2-1 sequences recovered trees with similar topology to previously published phylogenies of Neonectria and Corinectria . The results of this study indicate that all Neonectria and Corinectria tested are heterothallic based on our limited sampling and, as such, thallism cannot help explain the inevitable dominance of N. faginata in the BBD pathosystem.